The Influence Work Environment, Supervision, and Motivation on Employee Performance at The Human Resources Development Agency of North Sumatra Province - Willy Yusnandar (Journal of International Conference Proceedings (JICP), 2022)
This study means to decide if there is an impact of the workplace, management, and inspiration on worker execution at the HR Advancement Organization of North Sumatra Area. The methodology utilized is an affiliated methodology. The populace in this study were all long-lasting workers of the HR Advancement Organization, adding up to 82 individuals. the example was taken utilizing the immersed inspecting strategy (complete testing), the all-out populace was just 82 workers, so it is plausible to take the entire to be examined without taking a specific number of tests. What's more, utilized various straight relapse strategy, old style supposition test, t test (halfway), f test (synchronous), and coefficient of assurance with the assistance of SPSS 24.00 programming (statical item and administration arrangement). In view of the consequences of the review, it tends to be reasoned that to some degree, workplace, management, inspiration affect worker execution at the HR Improvement Organization of North Sumatra Region. All the while, workplace, management, inspiration essentially affect representative execution at the HR Advancement Organization of North Sumatra Region. Keywords:  Workplace, Oversight, Inspiration, Execution